The State Itself as a Vulnerable Subject? Existential Resilience under International Law. - Green, Alex (Modern Law Review, 2026)
This paper proposes a new framework for analysis of the law governing State continuity, with particular reference to Small Island Developing States (SIDS) threatened with legal extinction as a result of rising sea‐levels. Prevailing wisdom suggests that if States were to lose their inhabitable land or permanently resident populations, their status under international law would thereby lapse. On such accounts, international law is presumed to be a collection of established norms responding 'neutrally', as it were, to the purely physical phenomenon of sea‐level rise. This paper rejects that view, advancing an account of State vulnerability and resilience that draws upon Martha Albertson Fineman's conception of the 'vulnerable subject' and the 'responsive state' within the domestic legal context. By making a shift of scale within vulnerability theory from 'individuals and the state' to 'States and the international legal order', all States themselves (that is, in addition to all individuals) can be conceptualised as vulnerable artificial entities in relation to which international law can be more or less 'responsive'. From this perspective, the existential resilience of States must be recognised as contingent upon international law's institutional and regulatory structure, which itself results from the collective choices and ongoing dispositions of States themselves.